Role of CNR1 polymorphisms in moderating the effects of psychosocial adversity on impulsivity in adolescents - Buchmann, Arlette; Schmidt, Martin H.; Banaschewski, Tobias; Brandeis, Daniel; Laucht, Manfred (Journal of neural transmission, 2014)
Enhanced endocannabinoid signaling has been implicated in typically adolescent behavioral features such as increased risk-taking, impulsivity and novelty seeking. Research investigating the impact of genetic variants in the cannabinoid receptor 1 gene (CNR1) and of early rearing conditions has demonstrated that both factors contribute to the prediction of impulsivity-related phenotypes. The present study aimed to test the hypothesis of an interaction of the two most studied CNR1 polymorphisms rs806379 and rs1049353 with early psychosocial adversity in terms of affecting impulsivity in 15-year-olds from an epidemiological cohort sample followed since birth. In 323 adolescents (170 girls, 153 boys), problems of impulse control and novelty seeking were assessed using parent-report and self-report, respectively. Exposure to early psychosocial adversity was determined in a parent interview conducted at the age of 3 months. The results indicated that impulsivity increased following exposure to early psychosocial adversity, with this increase being dependent on CNR1 genotype. In contrast, while individuals exposed to early adversity scored higher on novelty seeking, no significant impact of genotype or the interaction thereof was detected. This is the first evidence to suggest that the interaction of CNR1 gene variants with the experience of early life adversity may play a role in determining adolescent impulsive behavior. However, given that the reported findings are obtained in a high-risk community sample, results are restricted in terms of interpretation and generalization. Future research is needed to replicate these findings and to identify the mediating mechanisms underlying this effect.